Pengembangan Modul dan Jobsheet Instalasi Motor Listrik Berbasis Project Based Learning Di SMKN 1 Cinangka - Idris Shuhada; Mohammad Fatkhurrokhman; Endi Permata (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of R&D research is to produce learning media products in the form of PJBL-based IML modules and jobsheets, to determine the level of expert feasibility, practicality and effectiveness in PJBL-based learning to determine whether the products made are suitable for use in learning so as to facilitate students in the learning process. The research method used is the Hannafin & Peck development model which has 3 stages of needs analysis, design, development and implementation. The results showed that the level of feasibility of the module material and IML jobsheets based on the assessment of material experts averaged 0.78 in the "valid" category and 0.81 in the "very valid" category. The feasibility level of module media and job sheets based on all aspects of the assessment averaged 0.93 in the "very valid" category and 0.92 in the "very valid" category. the level of practicality of modules and job sheets by educators obtained an average of 91% in the "very practical" category and 90% in the "very practical" category. And the level of practicality of modules and job sheets by students obtained an average of 89.7% in the "very practical" category and 83.2% in the "very practical" category. the level of effectiveness of modules and jobsheets is 88%, it can be said that the use of modules and jobsheets is "effective/complete".